If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -1(2x + 3) = x + -6 Reorder the terms: 5x + -1(3 + 2x) = x + -6 5x + (3 * -1 + 2x * -1) = x + -6 5x + (-3 + -2x) = x + -6 Reorder the terms: -3 + 5x + -2x = x + -6 Combine like terms: 5x + -2x = 3x -3 + 3x = x + -6 Reorder the terms: -3 + 3x = -6 + x Solving -3 + 3x = -6 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -3 + 3x + -1x = -6 + x + -1x Combine like terms: 3x + -1x = 2x -3 + 2x = -6 + x + -1x Combine like terms: x + -1x = 0 -3 + 2x = -6 + 0 -3 + 2x = -6 Add '3' to each side of the equation. -3 + 3 + 2x = -6 + 3 Combine like terms: -3 + 3 = 0 0 + 2x = -6 + 3 2x = -6 + 3 Combine like terms: -6 + 3 = -3 2x = -3 Divide each side by '2'. x = -1.5 Simplifying x = -1.5
| -97=-6(x+8)-7 | | 2k^2+9k=7 | | 5r^2-36r-32=0 | | 253=-2-5(7k+5) | | n^2-13n+50=0 | | -z+4=26 | | -3(8y-5)=4(1-7y)+14 | | Vf=0+0*20 | | 100x+90-x=99 | | 1+3n=1+3n | | 12+2[6+7(x+1)]=0 | | (X+21)+(x+61)+(X+23)=180 | | 1/4x^4-4 | | x-6=4x-2x-9 | | -21x+18x=3(-6-2x) | | 2.9x+4.5x= | | 2b(2a-x)=x(b-a)+a(x+b) | | X^2/3=10 | | 5(x-7)+6=5x-23 | | (2x+3)*(4x+7)=8x^2-5 | | X+(X+55)+(X+38)=180 | | 14/5x−14=4/5x−7/4 | | 12=7m-1+6m | | U=2a+2b | | X+3x-4=5(x+2) | | 6y-2=20 | | 18(2x+6)=6(3x+30) | | 40p-5=-5p-5 | | lne^4/5 | | 3x+7+5x=11+4x+8 | | 2x-6x=-2x | | 26+X^2=90 |